A Study of The Relationship Between Weakness in The Trunk Stabilising Muscles and Back Injuries Lumbar Injuries Among Boxers in Baghdad Clubs - Abbas Ali Mohammed (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
The aim of the study was to investigate the relationship between trunk muscle strength and lower back pain among boxers in Baghdad clubs, by measuring trunk muscle strength, assessing the level of lower back pain in the study sample, and identifying the nature of the correlation between the two variables. The researcher employed a descriptive approach using correlational methods, as this was appropriate to the nature and objectives of the study. The study population consisted of boxers officially registered with clubs in Baghdad and affiliated with the Iraqi Boxing Federation. The research sample was selected using a purposive sampling method and comprised eight boxers aged between 18 and 35 with at least two years’ training experience. The researcher used a series of physical tests to measure trunk muscle efficiency, namely: the forward trunk stability test, the lateral trunk stability test and the Bering-Sørensen test, as well as the Visual Analogue Scale (VAS) and a specific questionnaire to record low back pain. After collecting and statistically analysing the data using the arithmetic mean, standard deviation, percentage and Pearson’s correlation coefficient, the results showed that 87.5% of the sample had reduced trunk muscle efficiency compared to the levels recommended for athletes. It was also observed that 87.5% of the boxers suffered from lower back pain to varying degrees. The results demonstrated a strong, statistically significant inverse correlation between trunk muscle efficiency and lower back pain, with correlation coefficients ranging from (-0.74) to (-0.85); the Bearing-Sørensen test was the one most strongly associated with lower back pain. The researcher concluded that reduced trunk muscle function is associated with higher levels of lower back pain in boxers, and that weakness in the erector spinae and lateral trunk muscles may be an important factor associated with the onset of this pain. The researcher recommends the inclusion of core muscle strengthening and stability exercises in boxers’ training programmes, the adoption of core muscle function tests as a means of periodic assessment, as well as the provision of medical supervision and rehabilitation in boxing clubs to reduce lower back pain and improve sporting performance.